If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(c + 1) = 8c + -6 Reorder the terms: 9(1 + c) = 8c + -6 (1 * 9 + c * 9) = 8c + -6 (9 + 9c) = 8c + -6 Reorder the terms: 9 + 9c = -6 + 8c Solving 9 + 9c = -6 + 8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8c' to each side of the equation. 9 + 9c + -8c = -6 + 8c + -8c Combine like terms: 9c + -8c = 1c 9 + 1c = -6 + 8c + -8c Combine like terms: 8c + -8c = 0 9 + 1c = -6 + 0 9 + 1c = -6 Add '-9' to each side of the equation. 9 + -9 + 1c = -6 + -9 Combine like terms: 9 + -9 = 0 0 + 1c = -6 + -9 1c = -6 + -9 Combine like terms: -6 + -9 = -15 1c = -15 Divide each side by '1'. c = -15 Simplifying c = -15
| 4x-2x=570 | | -4.4z+5.9=-4.9z+2.9 | | 120=15/1/2 | | 3(x-1)-2(3x+2)=5(1-x) | | 1+3(-5z-3)=-5(5z+6)+3 | | w-3x-2y+2z=0 | | 4x15x1/2 | | 31y-(-1+10y)=-20 | | -6x=-3x-15 | | t=-16t^2+82t | | 9x-4=2t+3 | | 6y-23=14 | | -10(3-3x)+3(5x-4)=x | | 2X^2+4X+X=26 | | -2.2(y+14)=0.5(y+0.5) | | 208/6+8=x | | x+4-3=6(5) | | 5x^2+3x=6x^2+8 | | X+7-4=-2x+-5x+1 | | x-.12x=158400 | | -4v+20=-8v | | 2x+3y+2-y-5x-8= | | 4^2+8/2 | | 3(2x-5)=4(x-4)-6 | | 64a-21a= | | x=4x-4 | | 3(12-y)=8+3y | | -10z+9(4+3z)=x | | 61a-21a= | | 32=2+4+q | | 8+6+x=208 | | 4n-4=6n |